2023
DOI: 10.18502/ijph.v52i1.11671
|View full text |Cite
|
Sign up to set email alerts
|

Lncrna NEAT1 Regulates Th1/Th2 in Pediatric Asthma by Targeting MicroRNA-217/GATA3

Abstract: Background: The imbalance of immune response between helper Th1 and Th2 cells is the direct cause of asthma. It was closely related to abnormal expression of lncRNAs. However, whether lncRNAs can regulate Th1/Th2 balance in pediatric asthma remains to be investigated. Methods: Peripheral blood samples were collected from children with asthma and normal volunteers at the Children’s Hospital of Shaanxi Provincial People’s Hospital (Xi’an, China) in 2020. The qRT-PCR was used to detect the expression of lnc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…The interplay between PPARG and AKT1 is also evident in the context of cancer, with studies identifying their association in colorectal cancer, acute myeloid leukemia, and breast cancer [27][28][29]. Additionally, the involvement of PPARG in cellular signaling pathways related to COVID-19 severity and hepatolenticular degeneration underlines its significance beyond traditional signaling networks [30,31].…”
Section: Ppar Researchmentioning
confidence: 99%
“…The interplay between PPARG and AKT1 is also evident in the context of cancer, with studies identifying their association in colorectal cancer, acute myeloid leukemia, and breast cancer [27][28][29]. Additionally, the involvement of PPARG in cellular signaling pathways related to COVID-19 severity and hepatolenticular degeneration underlines its significance beyond traditional signaling networks [30,31].…”
Section: Ppar Researchmentioning
confidence: 99%
“…Studies have reported that asthma patients often experience disruption in the Th1-Th2 balance, which is also implicated in the onset and progression of asthma. 11,12 Given these factors, we conducted the present study to investigate the clinical value of serum levels of MMP-9, TIMP-1, COX-2, and Th1-Th2 in reflecting the condition of asthma patients.…”
Section: Introductionmentioning
confidence: 99%